Corrosion Initiation Behavior of Thermal Control Oxidation Film of LA103Z Alloy - Wen, Chen; Bai, Jingying; Zhao, Kuo; Cui, Qingxin; Jiao, Baocheng; Wang, Xuguang; Zhang, Ligong (Frontiers in Materials, 2021)
The magnesium lithium thermal control oxidation is a commonly used conductive anti-corrosion treatment method for aerospace. The corrosion behaviors of thermal control oxidation films for LA103Z alloys were studied in 3.5% NaCl solution. The corrosion characteristics with different immersion time were characterized by using scanning electron microscopy, energy spectroscopy and electrochemical methods. The results showed that the corrosion of Mg-Li alloy with chemical oxidation film starts from pitting corrosion, gradually expands in depth in the early stage, forms corrosion holes, and then gradually develops into river-like morphology. In the last stage, the increasing corrosion products slow down the corrosion rate and gradually covers the entire sample surface. The corrosion product is mainly consisted with MgO, LiF, MgCl2. Comebined with the electrochemical characteristics, the corrosion mechanism was investigated.